Earnings management and corporate governance in family controlled public listed firms in Malaysia / Shakerin Ismail, Mohd Rashdan Sallehuddin and Ho Yong Zhou - Ismail, Shakerin; Sallehuddin, Mohd Rashdan; Zhou, Ho Yong (2015)
More than half of the Malaysian economy activities are dominated by family controlling firms. They are significant players in the building and rising of the nation economic growths. This study aims to capture the effectiveness of corporate governance mechanism in managing these companies. Better known as family controlled companies, earnings management quality is used to gauge their significance through assessing their board independence and also the role of CEO. Moreover, referring to available literatures, it is aimed to confirm or dispute the findings through keen observation from the Malaysian perspective. The findings suggest that the percentage of board independence has a weaker effect on earnings management in family controlled companies and CEO duality is less effective in reducing earnings management especially when the CEO is the member of the family. The result of this study may be useful for academics and industry players as a whole to evaluate the effectiveness of the current model used and for future references.